PERENCANAAN KEUANGAN PRIBADI: MEMAHAMI OBJEK FORMAL DAN MATERIAL DALAM KONTEKS KEHIDUPAN SEHARI-HARI - Paramita, Gemala; Musqari, Nurul (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This research highlights the importance of a holistic and interdisciplinary approach to financial education, especially for children, adolescents, and college students. Experiential learning methods have proven to be effective in improving financial literacy and behavior by practicing financial concepts in real situations. In addition, the relevant curriculum in college, which focuses on life events such as loan management, increases the effectiveness of learning. However, the limitations of this study include a reliance on secondary data and a lack of theoretical testing in various contexts. These results support the importance of developing more objective measurement methods and the relevance of a holistic approach in financial education to prepare individuals for future financial challenges.